From Chaos Towards Sense: A Learner-Centric Narrative Virtual Learning Space - Reiners, Torsten; Wood, Lincoln; Dron, J. (IGI Global, 2014)
Throughout educational settings there are a range of open-focused learning activities along with those that are much more closed and structured. the plethora of opportunities creates a confusing melee of opportunities for teachers as they attempt to create activities that will engage and motivate learners. In this chapter, the authors demonstrate a learner-centric narrative virtual learning space, where the unrestricted exploration is combined with mechanisms to monitor the student and provide indirect guidance through elements in the learning space. The instructional designer defines the scope of the story in which the teacher and learner create narratives (a sequence of actions and milestones to complete a given task), which can be compared, assessed, and awarded with badges and scores. The model is described using an example from logistics, where incoming orders have to be fulfilled by finding the good and delivering it to a given location in a warehouse. Preliminary studies showed that the model is able to engage the learner and create an intrinsic motivation and therewith curiosity to drive the self-paced learning.